(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the methodological foundations of teaching methods of redrawing (reconstructing) epures, the role of these methods in developing students’ spatial imagination and graphic literacy, and improved approaches based on modern pedagogical technologies. In addition, the effectiveness of projection replacement, rotational transformation, and plane-parallel translation methods in solving epure problems is analyzed from a scientific and methodological perspective.